Synthesis and Investigation of Colon Specific Polymeric Prodrug of Ibuprofen with Cyclodextrin - PRABHU, PRABHAKARA; NAYARI, HARISH; GULZAR AHMED, MOHD.; SATYANARAYANA, D.; NARAYANA CHARYULU, R.; SUBRAHMANYAM, E.V.S.; BHAT, K.I. (Asian Journal of Chemistry, 2010)
The carboxyl group of ibuprofen was conjugated to one of the hydroxyl groups of b-cyclodextrin using a coupling agent, carbonyldiimidazole. The direct coupling produced ibuprofen appended cyclodextrin conjugate in which the drug is selectively introduced at one of the secondary hydroxyl groups of cyclodextrin through an ester linkage. The aqueous solubility (0.1 % w/v) was much higher than that of ibuprofen and no appreciable release of drug was observed in the stomach and small intestinal homogenates of rats. On the other hand fast disappearance of conjugate and appearance of the drug was observed in the cecal and colon contents of rats. The present ibuprofen-cyclodextrin conjugate may be of the value as an orally administered colon specific polymeric prodrug and hence the direct effect of carboxyl group on the gastric mucosa can be avoided.